Ship Design Based on Extreme Waves - Imawan Santosa, Pramudya; Zaed Yuliadi, Mochamad; Fajar, Achmad; Suardi, Suardi; Ayu Nastiti, Yulia; Pranatal, Erifiive (Indonesian Journal of Maritime Technology, 2025)
Recent studies have revealed that extreme waves (also known as freak waves), with heights ranging from 20 to 30 meters, occur more frequently than previously assumed. Over the past decades, numerous large commercial vessels have been lost due to incidents involving such anomalous wave phenomena. However, the current design criteria outlined in the 2022 BKI (Biro Klasifikasi Indonesia) Consolidation still consider significant wave heights of less than 11 meters, which is increasingly recognized as inadequate for modern oceanic conditions. This study aims to evaluate and propose ship design parameters that account for extreme wave conditions by incorporating significant wave heights of up to 30 meters into the safety analysis. The methodology involves a comparative analysis between the conventional design standards and a revised model that integrates dynamic wave impact forces as a crucial factor in determining the structural dimensions and stability of ships. The findings indicate that designing ships with consideration of extreme wave scenarios is not only feasible but also necessary to enhance vessel resilience and reduce the risk of capsizing and sinking. This research underscores the urgent need for updating maritime safety regulations and design frameworks in response to evolving oceanographic realities, thereby contributing to the development of safer and more robust marine transportation systems.